A STUDY OF DRINKING WATER AMENITY IN THE RESETTLEMENTS ESTABLISHED OF DUDHAGANGA IRRIGATION DAM AFFECTED PEOPLE IN KOLHAPUR DISTRICT (MH) (International Journal of Food and Nutritional Sciences, 2022)
Civic amenities have been developed through long course of times. In the earlier stage of human being the number of civic amenities was limited but in the modern period it has been increased significantly. Economic growth and human development are strongly determined by the prevailing infrastructure and civic amenity is a part of infrastructure. Social life is linked and enriched by these amenities. The involuntary displacement disintegrates well traditional network of indispensable amenities. The rehabilitation and resettlement procedure of displaced people is implemented by concern authority. The provision of basic an amenity is a part of rehabilitation procedure. Civic amenities are the integral part of settlements which determine the standard of particular settlement. Here an effort has been made study the situation of drinking water amenity of resettlements of Dudhaganga dam affected people in Kolhapur districts.